The Effect of Electric Shocks Produced by Various Amperes and Voltages on Larvae of Anopheles arabiensis Patton and Culex quinquefasciatus Say (Diptera, Culicidae). - Abd Algadir, Mutaman Ali; Dafaalla, Khalid Osman; Abd Ellateef, Hamed Ahmed; Homida, Abd Elmonem Eltayeb; Abdalla, Abdalla Ibrahim (مجلة الجزيرة للعلوم الصحية; مجلد 13 عدد 1 (2017), 2017)
This study was carried to determine the response of Anopheles arabiensis and Culex quinquefasciatus larvae when exposed to electric shocks. Karkoug village was chosen for collection of Anopheles and Culex mosquitoes (larvae). The collected larvae were immediately transferred to the University of Gezira, Faculty of Engineering and Technology, Basic Science Laboratory, where the tests were run. The electric shocks were performed by using a current of 1, 2, and 3 amperes by using a power supply (Popular, PE-23005, Made in India). The voltages used in each experiment were, 20, 30, 40, 50, and 60 volts. The duration of the electric shock was 2 minutes. These tests were repeated for three times and the average was subjected to probit analysis. The results showed that, changing of the electric current from 1, 2 to 3 amperes was associated with the decreases of Lethal Electric Shocks of 50% of the population form 31.468, 26.488 and 27.357 volts, respectively on Anopheles larvae, while they were 29.04, 28.58, and 25.65 volts, on Culex larvae. Culex larvae were more susceptible to the electric shocks than Anopheles larvae. The electric shocks also shortened the life span of the produced adults of both Culex and Anopheles . Also, the electric shocks induced a state of sterility (fail to reproduce) on the subjected species.